PENGARUH LATIHAN DRIBBLE SLALOM dan LATIHAN DRIBBLE INDIVIDUAL TERHADAP KEMAMPUAN DRIBBLING PADA PEMAIN SSB BINA BAKAT KARI KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Febby Leonardo; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Researcher observartion and also information from coach, there are deficiency and weakness that contained in technical factors on the players, especially when they dribbling. The population in this research were all the players of SSB Bina Bakat Kari Kuantan Tengah Districts Kuantan Singingi Regency consist of 16 players. The technique used to determine the sample of this research is Total Sampling. Test done by dribbling ball over cones that has been determined distance. The purpose of the dribbling test is to measure the ability of dribbling quickly with changes in directions. Data analisis technique used t-test. Based on t-test produced t-count amount 2,595 with t-table 1.753 then Ha rejected, at alpha rate (α) 0.05. It can be conluded that there is significant effect of Dribble Slalom training and Individual Dribble exercise towards dribbling ability on the player SSB Bina Bakat Kari Kuantan Tengah Districts Kuantan Singingi Regency.Keywords : Dribble Slalom and Individual Dribble Exercise, Dribbling Ability